Material Selection and Design Considerations for Hydrogen Transportation Pipelines - Famisa, Ayodele Adesina (International Journal of Computing and Engineering, 2025)
Purpose: Hydrogen is increasingly recognized as a key energy carrier in the global transition to low-carbon energy systems. Efficient and safe hydrogen transportation is critical, with pipelines representing the most practical option for large-scale distribution. This study investigates material selection and design considerations for hydrogen transportation pipelines to ensure reliability, safety, and economic feasibility. Methodology: A qualitative, systematic review of peer-reviewed literature, industry standards, and technical reports from 2018–2025 was conducted, focusing on the mechanical, chemical, and structural behaviour of materials under hydrogen exposure. Comparative analysis evaluated carbon steels, stainless steels, nickel alloys, polymers, and composites with respect to hydrogen embrittlement, permeability, mechanical performance, cost, and compliance with standards such as ASME B31.12 and ISO 16111. Findings: Findings indicate that while carbon steels are cost-effective, they are highly susceptible to embrittlement, whereas austenitic stainless steels and nickel alloys offer superior hydrogen resistance at higher costs. Hybrid designs combining carbon steel exteriors with stainless or nickel alloy linings present an optimal balance of safety, durability, and cost. Unique Contribution to Theory, Practice and Policy: Recommendations include adopting hybrid materials, strict welding protocols, protective coatings, and real-time monitoring to enhance pipeline integrity and support sustainable hydrogen infrastructure development.